Controlled Semi-Presidentialism: The Case for Semi-Presidentialism Under the Indian Constitution - Gautam, Khagesh (Columbia Journal of Asian Law, 2015)
The objective of this article is to subject the proposition that the office of the Indian President has been reduced to, what in India is sometimes referred to as, a “rubber-stamp” office, whereby the President is mostly a ceremonial head of state without any active participation in the inner workings of the executive or legislative business of the country to close scrutiny via a lens of constitutional law. This article is divided into two parts. Part I of this article closely examines the Ceremonial Head position as laid out in the text of the Indian Constitution and various Supreme Court opinions. The legal evidence points to several contradictions. Part II of this article attempts to square these contradictions by making the case for a semi presidential reading of the Indian Presidency.